2021
DOI: 10.3390/ijms23010126
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Hypoxic and Pro-Inflammatory Priming of Mesenchymal Stem Cell-Derived Extracellular Vesicles in Inflammatory Arthritis

Abstract: Mesenchymal stem cells (MSCs) immunomodulate inflammatory responses through paracrine signalling, including via secretion of extracellular vesicles (EVs) in the cell secretome. We evaluated the therapeutic potential of MSCs-derived small EVs in an antigen-induced model of arthritis (AIA). EVs isolated from MSCs cultured normoxically (21% O2, 5% CO2), hypoxically (2% O2, 5% CO2) or with a pro-inflammatory cytokine cocktail were applied into the AIA model. Disease pathology was assessed post-arthritis induction … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 70 publications
0
15
0
Order By: Relevance
“…For instance, an EV suspension (corresponding to 5.0 × 10 5 of human BM-MSCs) injected into the knee joint of antigen-induced arthritis mice significantly reduced paw swelling and histopathological changes through the suppression of Th17 polarization and synovial cellular infiltration. 65 In CIA rats, a single intravenous injection of sEVs from human UC-MSCs dose-dependently reduced joint inflammation, synovial hyperplasia and cartilage destruction. Besides, these EVs decreased T-cell proliferation, promoted the apoptosis of these cells and increased the Treg/Th17 ratio.…”
Section: Administration Of Msc Evs Controls the Progression Of Experi...mentioning
confidence: 97%
See 1 more Smart Citation
“…For instance, an EV suspension (corresponding to 5.0 × 10 5 of human BM-MSCs) injected into the knee joint of antigen-induced arthritis mice significantly reduced paw swelling and histopathological changes through the suppression of Th17 polarization and synovial cellular infiltration. 65 In CIA rats, a single intravenous injection of sEVs from human UC-MSCs dose-dependently reduced joint inflammation, synovial hyperplasia and cartilage destruction. Besides, these EVs decreased T-cell proliferation, promoted the apoptosis of these cells and increased the Treg/Th17 ratio.…”
Section: Administration Of Msc Evs Controls the Progression Of Experi...mentioning
confidence: 97%
“…Therefore, EVs isolated from early-passage BM-MSCs are more immunosuppressive than those from late-passage cells while BM-MSCs in 3D cultures release more effective EVs compared with conventional 2D cultures. 37 Although recent research has suggested that normal culture conditions of MSCs are sufficient to isolate EVs with significant anti-arthritic activity in animal models, 65 different priming strategies have been used to improve their immunomodulatory properties and therapeutic potential. Pro-inflammatory priming induces important changes in the cargo of EVs and promotes the release of a higher percentage of sEVs compared to lEVs.…”
Section: Modifications Of Msc Evsmentioning
confidence: 99%
“…EVs isolated from MSCs were cultured normoxically (21% O 2 , 5% CO 2 ), and the AIA model was applied with normoxic EVs. These are associated with the establishment of TH17/Treg balance that resulted in reduced inflammation 68 …”
Section: Msct In Ramentioning
confidence: 99%
“…Moreover, since the concentration of MSC‐EV in the conditioned medium is typically low, scale‐out to hundreds of T‐flasks or multiplate flask systems is required, involving an extensive handling for feeding/harvesting procedures, to achieve significant final mass production. Additionally, several differences were observed, in terms of the MSC‐derived EVs cargo, between EVs isolated from culture supernatants of MSC expanded under different culture conditions, stressing the importance of controlling all culture process parameters to obtain a consistent EV content (Hyland et al, 2020; Kay et al, 2021). In this context, it turns necessary to move forward to fully controlled reactors (i.e., stirred tank reactors [STR]) to establish a reproducible and scalable process to produce MSC‐EV.…”
Section: Introductionmentioning
confidence: 99%